Economic and Social Aspects of Palm Oil IndustryL Indonesia's Palm Oil Trade in the Context of Economic Liberalization - Erna Maria Lokollo (Analisis Kebijakan Pertanian, 2013)
This paper aims to assess the palm oil trade in the world market, factors affecting Indonesia’s palm oil industry and trade, and how it can contribute to and benefit the sustainable agriculture development. Palm oil and palm kernel oil make up a third of total world production of oils and fats. During the last decade, the stock-production-import-export of palm oil in the world trade has increased to more than double in volumes and values. Other than being main producers, Indonesia and Malaysia are the two major exporters of palm oil in the world market with total shares of more than 80 percent of the total world export. Coupled with increasing demand for cooking oils, growing demand for palm oil derivatives-products has created a new challenge and opportunity for Indonesia to increase its competitiveness in the world market. Indonesia has and could continue to seize the opportunity to meet the increasing world market demand provided it can increase the ability to translate the new world market demand and adjust it to its domestic production facilities. The Indonesian policies of palm oil development must be directed, implemented and enforced with the focus to the downstream industries. The world concern of environmental degradation has triggered an RSPO forum and Indonesia responded through the ISPO to support the sustainable development. As the main producer, it is only fitting if Indonesia becomes and sets a price reference for sustainable palm oil traded in the world market.